ATURAN PERPAJAKAN ATAS NATURA DAN/ATAU KENIKMATAN DI INDONESIA: ISU DAN TANTANGAN - Gunawan, Florencia Irena (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
This research aims to identify various issues and challenges as a result of an adjustment within the imposition of Income Tax Article 21 (“PPh 21”) upon in-kind benefits in the form of treatment of benefits (facilities/service) and in-kind remuneration (goods), whereby prior to the enactment of Law Number 7 of 2021 on the Harmonization of Tax Regulation (“UU HPP”), in-kind benefits were not included as the object of PPh 21. This research focuses on the Ministry of Finance Regulation Number 66/2023 on Income Tax Treatment of Replacement or Reward in Connection with Work or Services Received or Obtained in the Form of In-Kind Benefits (“PMK 66/2023”) as a technical regulation derived from the UU HPP which regulates in more detail the imposition and collection of taxes on in-kind benefits. The provisions in PMK 66/2023 will be analyzed in a structured manner using the principles of an ideal tax system–consisting of: revenue productivity, equity, and ease of administration–in order to comprehensively identify the issues and challenges within the implementation of this regulation. This research concludes that the government's main goal in significantly changing the taxation rules on in-kind benefit is to meet revenue productivity. However, in fulfilling this, the principles of equity and ease of administration have not been properly realized, given the fact that there are number of issues in the PMK 66/2023, which need to be further addressed. Accordingly, this research provides theoretical and practical contributions to the further development of tax regulations on in-kind benefits, whereby expected to accommodate the various issues and challenges as identified in this research.